Our Quadratic is in the kind #ax^2+bx+c=0#. Once we complete the square, us take half of the #b# value, square it, and add it come both sides.

First, let"s subtract #20# native both sides. We get:

#x^2+12x =-20#

Half of #12# is #6#, and when us square #6#, we gain #36#. Let"s include this to both sides. We get:

#x^2+12x+36=-20+36#

Simplifying, we get:

#x^2+12x+36=16#

Now, we factor the left next of the equation. We think of two numbers that include up to #12# and also have a product the #36#. #6# and #6# room our two numbers.

We can now element this as:

#color(blue)((x+6)(x+6))=16#

Notice, what I have in blue is the same as #x^2+12x+36#. We have the right to rewrite this as:

#(x+6)^2=16#

Taking the square root of both sides, we get:

#x+6=-4# and #x+6=4#

Subtracting #6# from both political parties of the equations, us get:

#x=-10, x=-2#


Answer attach
*

Brandon
Mar 3, 2018

#x=-2# and also #x=-10#


Explanation:

By perfect the square, we always half the coefficient the #x#, placing it in brackets and squaring it, as a quadratic is always in the form #ax^2+bx+c#. Constantly remember to add the continuous of #(+20)# on the end:

#therefore# #x^2+12x -> (x+6)^2#

Also by perfect the square, we also take far the squared number of fifty percent of the ahead coefficient (the number in the brackets).

You are watching: Solve x2 + 12x + 6 = 0 using the completing-the-square method.

#(x+6)^2-36+20#

Simplifying terms:

#-36+20=-16#

Plugging this earlier in, removed the #-36# and also #20#:

#(x+6)^2-16#

This is in the perfect square form. You can constantly check this by widening out:

#(x+6)(x+6) -> x^2+6x+6x+36-16 -> x^2+12x+20#

#therefore# This complete the square kind is correct.

Solving; so far we know:

#(x+6)^2-16=0#

So we add #16# to resolve this, as we cannot solve when equal to 0.

#(x+6)^2=16#

As we do not desire squares brackets, the contrary of squaring is square rooting, and this cancels the end the squared brackets:

#(x+6)^2=16 -> x+6=pmsqrt16#

Always psychic the #pm# as soon as square rooting...

As we desire #x# on that own, we have to #-6# to eliminate it, transporting the #-6# to the various other side the the equation.

#x+6=pmsqrt16 -> x=-6pmsqrt16#

Always remember over there are mainly two solutions, together there is a plus and minus top top the answer.

#therefore# our answers are...

See more: Cle To Sfo (Cleveland To San Francisco) Flights From Cle To Sfo

#x=-6pmsqrt16# and #x=-6pmsqrt16#

But using our squared numbers:

#1^2=1xx1=1##2^2=2xx2=4##3^2=3xx3=9##4^2=4xx4=16# #sqrt16# have the right to be simplified additional as that is a squared number...